The Generation of Upward‐Propagating Whistler Mode Waves by Electron Beams in the Jovian Polar Regions. Issue 6 (12th June 2020) - Elliott, S. S.; Gurnett, D. A.; Yoon, P. H.; Kurth, W. S.; Mauk, B. H.; Ebert, R. W.; Clark, G.; Valek, P.; Allegrini, F.; Bolton, S. J.; Menietti, J. D.; Louarn, P.; et al.
Abstract: Upward‐moving energetic electrons with energies of 1 MeV and above were observed over the entire Jovian polar region. The electrons were found to be associated with intense broadband whistler mode waves, similar to terrestrial whistler mode auroral hiss. Upward‐propagating whistler mode hiss at Earth is known to be generated by upward‐moving, magnetic field‐aligned electron beams (from electric field‐aligned potentials), by a beam‐plasma instability at the Landau resonance. Assuming this process at Jupiter, we present a linear stability analysis, showing the electron distribution functions (based on inverted‐V observations made by the Juno Jovian Auroral Distributions Experiment, JADE‐E, instrument) are unstable. The polarization of the modeled waves is consistent with whistler mode hiss (right‐hand circularly polarized). From the results of the linear stability analysis, we find that the calculated growth rates are sufficient to produce the observed whistler mode waves. Key Points: Upgoing electron beams can generate upward‐propagating whistler mode waves over the Jovian polar cap region Numerical simulations show the electron beams are unstable and capable of producing the observed whistler mode waves Large growth rates are found for Landau ( n = 0) resonance